The Influence of Motivation And Supervision On Employees' Work Productivity CV Cemara Alumunium Tegal City - Hendrikus Putra Cromain (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2024)
This research aims to analyze the influence of motivation and supervision on the work productivity of employees at CV Cemara Alumunium Tegal City partially and simultaneously. The population in this study were CV employees. Cemara Alumunium Tegal City numbered 36 people with 10 permanent employees and 26 freelancers, with the sampling technique used, namely the saturated sample technique or census, where the entire population was sampled as 36 respondents. The analytical tool used is multiple linear regression with a partial test tool (t test) and a simultaneous test tool (F test). The results of the analysis partially show that there is a positive and significant influence on the motivation variable on employee work productivity. This is shown by t count > t table (2.516 > 2.032) with a sig value. 0.017 (p<0.05), then Ho is rejected and Ha is accepted, and the supervision variable has a positive and significant influence on the employee work productivity variable. This is shown by t count > t table (3.951 > 2.032) with a sig value. 0.000 (p<0.05), then Ho is rejected and Ha is accepted. The results of the subsequent analysis simultaneously show that there is a positive and significant influence of motivation variables and supervision variables together on employee work productivity variables. This is shown by t count > t table (21.556 > 3.284) with a sig value. 0.000 (p<0.05), then Ho is rejected and Ha is accepted.